Metamodern audience response toward Nizar Qabbani’s poetry on Instagram reels: Literary reception study - Az-Zahra, Sabrina; Hasyim, Muhammad (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
This research examines the metamodern audience reception of Nizar Qabbani’s modern Arabic poetry through Instagram Reels, with a focus on the emergence of metamodern sensibilities in the response to his poetry. The study employs a reader-response approach and is multifaceted, integrating literary reception theory with the concepts of Jauss and Iser’s reception theory while also incorporating metamodern sensibilities to analyse audience responses. The analysis of audience comments reveals that the fusion of three domains (Jauss reception, Iser reception and metamodern sensibility) provides a comprehensive understanding of metamodern audience responses. The findings demonstrate that the amalgamation of Jauss and Iser’s reception categorised into the following three domains: (1) historical perception and reality of fiction, (2) horizon of expectation and implied reader, and (3) aesthetic distance and blanks, in combination with metamodern audiences, generate meaning through multiple types of responses, which researchers have categorised into various types. These categories reflect the intricate interplay between Jauss’s macro-level form of reception, Iser’s micro-level form of reception, and the articulation of metamodern sensibilities.